Adaptation Challenges and Coping Strategies Among First-Year Nursing Students: Assessing the Impact of a Structured Teaching Program in Noida, Uttar Pradesh - Ijtsma, Hamse (Journal of Educational Research and Policies, 2025)
Many individuals perceive the transition from senior secondary school to college as a crucial milestone in their development from adolescence to adulthood. For many first-year college students, the first day of classes can be a stressful experience. The objective of this study was to evaluate the effectiveness of a structured teaching program designed to address adaptation problems and coping strategies among first-year nursing students at selected colleges in Noida. A pre-experimental one-group pre-test and post-test design was employed for the study. A total of 40 students were selected using a simple random sampling method to complete a self-structured questionnaire. Descriptive and inferential statistics were utilized for data analysis. The majority of first-year students faced serious academic problems, with 60% reporting severe social problems, 50% experiencing mild emotional problems, 60% struggling with moderate financial problems, and 50% lacking adequate coping mechanisms. The mean pre-test and post-test scores of first-year nursing students differed significantly, according to the results. An efficient way to increase understanding of adaption problems and coping mechanisms was through the use of a structured teaching program.